Factors Influencing Stakeholders Decision to Invest in Residential Properties: A Perceptual Analysis of Flood-Risk Areas - Oyetunji A.K.; Amaechi C.V.; Dike E.C.; Ayoola A.B.; Olukolajo M.A. (MDPI, 2024)
The ground can become saturated during prolonged downpours. If sewers and drains are unable to cope, overflows will be inevitable. This situation could affect properties that are not designed to cope with flood hazards. It is pertinent that property investors should consider flooding and the likelihood of its occurrence when making investment decisions. The question is, do they? This study investigates the factors that influence residential property investment decisions in flood-risk areas of the Lagos metropolis. This is achieved by evaluating a range of locational, neighbourhood, structural, market/economic, behavioural, and risk characteristics in the determination of residential property investment choices in areas that are susceptible to flood risk. The data were sourced from private investors and registered real estate agents in the risk areas of Lagos State, Nigeria. Structured questionnaires were used for data collection purposes, and only valid responses were used for the data analysis. The results show that the availability of infrastructural supply, the crime rate in the neighbourhood, and the property location could significantly motivate investors decisions with respect to property investment in flood-risk areas. The perception plot shows that behavioural factors have the highest bearing on the investment decisions for private investors, at 4.4, followed by economic factors at 4.0 and locational factors at 3.6. The plot also shows that neighbourhood factors have the highest bearing on the investment decisions for estate agents, at 4.6, followed by economic factors at 4.0 and locational factors at 3.6. This implies that there are various degrees of correlation between the factors examined in this study. It is important to highlight the relevance of the findings for the field and pave the way for future scientific development in flood-risk management. 2023 by the authors.